Identificação e avaliação de propriedades de polissacarídeos sulfatados de diferentes fontes naturais que possibilitem sua aplicabilidade biotecnológica - Santos, Nednaldo Dantas dos (2012)
Sulfated polysaccharides (SP) are widely distributed in animals and seaweeds tissues. These polymers have been studied in light of their important pharmacological activities, such as anticoagulant, antioxidant, antitumoral, anti-inflammatory, and antiviral properties. On other hand, SP potential to synthesize biomaterials like as nanoparticules has not yet been explored. In addition, to date, SP have only been found in six plants and all inhabit saline environments. However, the SP pharmacological plant activities have not been carrying out. Furthermore, there are no reports of SP in freshwater plants. Thus, do SP from marine plants show pharmacological activity? Do freshwater plants actually synthesize SP? Is it possible to synthesize nanoparticles using SP from seaweed? In order to understand this question, this Thesis was divided into tree chapters. In the first chapter a sulfated polysaccharide (SPSG) was successfully isolated from marine plant Halodule wrightii. The data presented here showed that the SPSG is a 11 kDa sulfated heterogalactan contains glucose and xylose. Several assays suggested that the SPSG possessed remarkable antioxidant properties in different in vitro assays and an outstanding anticoagulant activity 2.5-fold higher than that of heparin Clexane® in the aPTT test; in the next chapter using different tools such as chemical and histological analyses, energy-dispersive X-ray analysis (EDXA), gel electrophoresis and infra-red spectroscopy we confirm the presence of sulfated polysaccharides in freshwater plants for the first time. Moreover, we also demonstrate that SP extracted from E. crassipes root has potential as an anticoagulant compound; and in last chapter a fucan, a sulfated polysaccharide, extracted from the brown seaweed was chemically modified by grafting hexadecylamine to the polymer hydrophilic backbone. The resulting modified material (SNFuc) formed nanosized particles. The degree of substitution for hydrophobic chains of 1H NMR was approximately 93%. SNFfuc-TBa125 in aqueous media had a mean diameter of 123 nm and zeta potential of -38.3 ± 0.74 mV, measured bydynamic light scattering. Tumor-cell (HepG2, 786, H-S5) proliferation was inhibited by 2.0 43.7% at SNFuc concentrations of 0.05 0.5 mg/ mL and RAEC non-tumor cell line proliferation displayed inhibition of 8.0 22.0%. On the other hand, nanogel improved CHO and RAW non-tumor cell line proliferation in the same concentration range. Flow cytometric analysis revealed that this fucan nanogel inhibited 786 cell proliferation through caspase and caspaseindependent mechanisms. In addition, SNFuc blocks 786 cell passages in the S and G2-M phases of the cell cycle